2020
DOI: 10.1161/circep.120.008646
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Very Late Recurrence of Atrial Fibrillation Following Cryoballoon Pulmonary Vein Isolation

Abstract: Background - A very late recurrence (VLR) of atrial fibrillation (AF) is considered present when the first recurrence of AF occurs ≥ 12 months following ablation. Prior studies characterizing VLR have not used an implantable loop recorder (ILR) for ECG monitoring. Thus, it is unknown whether VLR truly occurs or whether these patients have simply had unrecognized AF. Our objective was to assess the incidence and predictors of VLR in patients who underwent cryoballoon (CB) pulmonary vein isolation (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…We studied a larger number of patients than previously reported, included intra procedural electrophysiological findings, and examined predictors of VLRAF. Although this is the first report on the association between LVAs and VLRAF, we consider that our results are consistent with previous findings to date, given that hypertension and diabetes, whose association with VLRAF is known, are also reported to be predictors of LVAs 27–29 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We studied a larger number of patients than previously reported, included intra procedural electrophysiological findings, and examined predictors of VLRAF. Although this is the first report on the association between LVAs and VLRAF, we consider that our results are consistent with previous findings to date, given that hypertension and diabetes, whose association with VLRAF is known, are also reported to be predictors of LVAs 27–29 …”
Section: Discussionsupporting
confidence: 93%
“…Although this is the first report on the association between LVAs and VLRAF, we consider that our results are consistent with previous findings to date, given that hypertension and diabetes, whose association with VLRAF is known, are also reported to be predictors of LVAs. [27][28][29]…”
Section: Clinical Factors Associated With Vlrafmentioning
confidence: 99%
“…21 Comorbidities and hypertension are associated with late recurrences of AF, that is, over 1 year after ablation. [22][23] Multiple comorbidities (CHA 2 DS 2 -VASc >2) have been seen to correlate with an increased degree of left atrial fibrosis, which has been found to be a predictor of AF after ablation. 24 These results suggest that recurrences in these patients could be associated with atrial remodeling.…”
Section: 3mentioning
confidence: 99%